Glutaric Acidemia, Pathogenesis and Nutritional Therapy - Li, Qian; Yang, Chunlan; Feng, Lijuan; Zhao, Yazi; Su, Yong; Liu, Hong; Men, Hongkang; Huang, Yan; Körner, Heinrich; Wang, Xinming (Frontiers in Nutrition, 2021)
Glutaric acidemia (GA) are heterogeneous, genetic diseases that present with specific catabolic deficiencies of amino acid or fatty acid metabolism. The disorders can be divided into type I and type II by the occurrence of different types of recessive mutations of autosomal, metabolically important genes. Patients of glutaric acidemia type I (GA-I) if not diagnosed very early in infanthood, experience irreversible neurological injury during an encephalopathic crisis in childhood. If diagnosed early the disorder can be treated successfully with a combined metabolic treatment course that includes early catabolic emergency treatment and long-term maintenance nutrition therapy. Glutaric acidemia type II (GA- II) patients can present clinically with hepatomegaly, non-ketotic hypoglycemia, metabolic acidosis, hypotonia, and in neonatal onset cardiomyopathy. Furthermore, it features adult-onset muscle-related symptoms, including weakness, fatigue, and myalgia. An early diagnosis is crucial, as both types can be managed by simple nutraceutical supplementation. This review discusses the pathogenesis of GA and its nutritional management practices, and aims to promote understanding and management of GA. We will provide a detailed summary of current clinical management strategies of the glutaric academia disorders and highlight issues of nutrition therapy principles in emergency settings and outline some specific cases.